Relationship between Family Support and Medication Adherence in Tuberculosis Patients - Muhammad Sahlan Zamaa; Dewi Purnama Windasari; Esse Puji Pawenrusi; Aminullah Aminullah; Zulfiqrie Iskandar (Jambura Nursing Journal, 2023)
Tuberculosis (TB) is an infectious disease that attacks the respiratory system with a high incidence in Indonesia.. Tuberculosis treatment requires a long time, at least 6 months causing many patients to stop taking drugs. One of the factors that causes patients to drop out of medication is the lack of family support while the patient is undergoing treatment. This study aims to determine the relationship between family support and medication adherence in TB patients. This type of research is analytic research with a cross sectional approach. The population in this study were 60 TB patients with a large sample of 52 respondents taken using accidental sampling technique. Data collection used an observation sheet and was analyzed using the fisher exact test. The statistical test results showed a ρ value of 0.007 (p